(untitled) (Journal of the College of Basic Education, 2026)
Dialogue is considered one of the most important pillars of human understanding and communication between individuals and societies. The values ​​of social life cannot be tested or stabilized without a clear exchange of opinions and ideas. The need for dialogue has increased in this era due to the diversity of all aspects, the intertwining of parties, and the rise of the social ladder, which now threatens social services. Hence, the importance of difference as a fundamental civilizational tool for establishing the values ​​of tolerance, coexistence, and the rejection of violence… The choice of this topic stems from the many theories of intellectual property rights witnessed in contemporary reality, both among followers of the same religion and among followers of different religions and cultures. Through this research, I attempt to shed light on the philosophy of dialogue in Islam, which relies on the most sublime bonds, fundamentally based on a philosophy of dialogue based on cooperation, justice, and compassion. The importance and objectives of this research lie in demonstrating how the Islamic religion has established a dialogue-based approach based on Quranic and prophetic principles, which uphold human dignity, reason, and freedom of choice. This research seeks to. Uncover the origins of disagreement in the Quran and Sunnah- Analyzing the principles and objectives of Islamic dialogue- -Explaining the difference between Islamic dialogue and forms of sterile debate. Highlighting the role of dialogue in disseminating databases.- This research relies on a descriptive analytical approach, through analyzing Quranic and Hadith texts related to dialogue, in addition to employing Islamic jurisprudential and intellectual references that address dialogue. Some philosophical models are also employed to understand concepts and the concept, and to link them to contemporary reality.